2020
DOI: 10.1021/acs.nanolett.0c00227
|View full text |Cite
|
Sign up to set email alerts
|

High Power Thermoelectric Generator Based on Vertical Silicon Nanowires

Abstract: Thermoelectric generators, which convert heat directly into electrical power, have great potentialities in the energy harvesting field. The exploitation of these potentialities is limited by the materials currently used, characterized by good thermoelectric properties, but also by several drawbacks. This work presents a silicon-based thermoelectric generator, made of a large collection of heavily p -doped silicon nanostructures. This macroscopic device (area of several mm 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 44 publications
0
53
0
Order By: Relevance
“…Previous works on semiconductor nanowires have shown that it is possible to modulate the thermoelectric properties with a gate voltage [ 29 , 30 , 31 , 32 , 33 ] and achieve power factors of the order of 1 mW/K m. However, in these systems, an increase in electrical conductivity was accompanied by a decrease in the Seebeck coefficient. For multilayer metallic nanowires, the giant magneto-transport effects lead simultaneously to an increase in the Seebeck coefficient and a decrease in the electrical resistance, which allows a strong increase in the power factor following the application of a magnetic field.…”
Section: Resultsmentioning
confidence: 99%
“…Previous works on semiconductor nanowires have shown that it is possible to modulate the thermoelectric properties with a gate voltage [ 29 , 30 , 31 , 32 , 33 ] and achieve power factors of the order of 1 mW/K m. However, in these systems, an increase in electrical conductivity was accompanied by a decrease in the Seebeck coefficient. For multilayer metallic nanowires, the giant magneto-transport effects lead simultaneously to an increase in the Seebeck coefficient and a decrease in the electrical resistance, which allows a strong increase in the power factor following the application of a magnetic field.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, Donmez et al have measured the maximum power densities of Si NWs, SiGe NWs, and Si micro-beam-based µTEG with values of 41.2, 45.2, and 34.5 µW/ cm 2 , respectively, at a hot plate temperature of 100 • C (Donmez Noyan et al, 2019). A two-leg µTEG has been fabricated based on vertical Si NW forest where the achieved power output is 0.25-0.5 µW/(cm 2 K 2 ) with the NW length from 25 to 6.5 µm (Elyamny et al, 2020). By shortening Si NW to sub-µm length, a planar µTEG achieved the power density of 12 µW/cm 2 with T = 5 K (Tomita et al, 2018b).…”
Section: Te Properties For Nws and Tegmentioning
confidence: 99%
“…Simulations and analytic models based on the finite element method (FEM) have been applied for the risk/cost reduction in fabrication, and the data are compared with the experimental results (Tomita et al, 2018b;Donmez Noyan et al, 2019;Elyamny et al, 2020). In a recent study, with the 3-D FEM device simulation software COMSOL Multiphysics, a research group has analyzed the thermal distribution and power generation of Si NWs TEG with varied parameters (Zhang et al, 2018).…”
Section: Te Properties For Nws and Tegmentioning
confidence: 99%
“…Unfortunately MACE yields very unreliable results at such high doping concentrations. In the case of p + doping, parameters for a satisfactory fabrication of monocrystalline SiNW forests have been found [17]. However, the reliable fabrication of n + SiNWs by MACE is still an open issue [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Metal-assisted chemical etching (MACE) [ 11 14 ] of silicon is very promising because it gives the opportunity to fabricate large numbers of nanowires with high aspect ratio, perpendicular to a silicon substrate, that is, so-called silicon nanowire (SiNW) forests. The process is very suitable for the large-scale fabrication of nanostructured devices useful for several applications, such as sensing, photovoltaics, energy storage (supercapacitors), and, in particular, thermoelectric applications [ 15 17 ]. There are two main requirements to the fabrication of a leg for a thermoelectric generator that is based on a large number of silicon nanowires perpendicular to a substrate: 1) Electrical contacts need to fabricated on the top of a silicon nanowire forest, which can be achieved by copper electrodeposition [ 18 ].…”
Section: Introductionmentioning
confidence: 99%